(untitled) (Comprehensive Journal of Science, 2025)
This study aims to examine the impact of effective administrative leadership on improving the performance of employees at the Higher Institute of Science and Technology – Al Zahraa. The research analyzes the level of leadership practices among top and middle management and their influence on employees’ productivity and performance quality. The descriptive-analytical method was used, and data were collected through a questionnaire distributed to a sample of employees at the institute. The findings revealed that effective administrative leadership—represented by communication, motivation, decision-making, and work management—significantly contributes to enhancing job performance, increasing commitment, and improving task quality. The study also found a statistically significant correlation between administrative leadership and employees’ performance levels. It recommends strengthening leadership training programs, improving motivation mechanisms, and activating organizational communication to sustainably enhance employee performance.